2002
DOI: 10.1021/jf011462e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grape Vitis vinifera L. DNA in Must Mixtures and Experimental Mixed Wines Using Microsatellite Markers

Abstract: Because wine quality highly relies on the varietal composition of the must, the development of methods allowing the authentication of varieties in musts and wines would be of great value as a guarantee of quality. Microsatellite markers have already been applied to the authentication of grape juices (Faria, M. A.; Magalhães, R.; Ferreira, M. A.; Meredith, C. P.; Ferreira Monteiro, F. J. Agric. Food Chem. 2000, 48, 1096-1100) and to the analysis of experimental wines (Siret, R.; Boursiquot, J. M.; Merle, M. H.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 22 publications
(27 reference statements)
6
51
1
Order By: Relevance
“…In this study, profiles generated by all microsatellite loci matched between samples from the same genotypes, reinforcing the view that nuclear SSR markers are suitable for certification purposes, as suggested by Baleiras-Couto and Eiras-Dias (2006), Savazzini and Martinelli (2006), and Siret et al (2000Siret et al ( , 2002.…”
Section: Nuclear Ssrsupporting
confidence: 74%
See 2 more Smart Citations
“…In this study, profiles generated by all microsatellite loci matched between samples from the same genotypes, reinforcing the view that nuclear SSR markers are suitable for certification purposes, as suggested by Baleiras-Couto and Eiras-Dias (2006), Savazzini and Martinelli (2006), and Siret et al (2000Siret et al ( , 2002.…”
Section: Nuclear Ssrsupporting
confidence: 74%
“…The must DNA sample concentrations ranged from 211 to 401 ng μL −1 . The must DNA yields were higher than those reported by other authors using similar samples (Faria et al 2000(Faria et al , 2008Garcia-Beneytez et al 2002;Siret et al 2002), ranging from 10 to 20 μg mL −1 of starting material. One of the reasons that may explain the higher yields obtained may be the fact that we have used immediately frozen fresh must samples, which preserved high-quality DNA.…”
Section: Dna Extraction and Quantificationcontrasting
confidence: 71%
See 1 more Smart Citation
“…Late, same microsatellite loci and similar method was used as an attempt to analyze a grape variety Vitis vinifera in commercial must mixtures and also in experimental mixtures. The present study has proved that, DNA can be analyzed from the experimental wines until the last day of the fermentation process [30]. Vitis vinifera nine cis epoxycarotenoid dioxygenase2 (VvNCED2) was used as reference gene in authentication of grape variety in a wine samples.…”
Section: Res Dev Materials Sci Research and Development In Materials Sciencementioning
confidence: 83%
“…DNA analysis has recently emerged as a novel and efficient technology in food tests, initially developed for the detection of GM food ingredients (Hemmer, 1997;Hurst, Knight, & Bruce, 1999;Peano, Samson, Palmieri, Gulli, Marmiroli, 2004), and now expanding to species and cultivar discrimination of raw material in food and feed (Busconi et al, 2003;Hunt, Parkes, & Davies, 1997;Krcmar & Rencova, 2003;Pasqualone, Montemurro, Caponio, & Blanco, 2004;Siret, Gigaud, Rosec, & This, 2002).The prerequisite for DNA analysis of processed food is the availability of high quality genomic DNA. Studies on DNA extraction from wheat flour and baked products (Tilley, 2004) and soybean and maize products (Peano et al, 2004) demonstrated that there is significant DNA degradation during food processing, particularly when chemical and enzymatic treatment is applied, and that sometimes the extracted DNA is only useful for amplification of DNA fragment of less than 300 bp.…”
Section: Introductionmentioning
confidence: 99%